2005
DOI: 10.1021/bm0503423
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast Adhesion on Poly(l-lactic Acid)/Polystyrene Demixed Thin Film Blends:  Effect of Nanotopography, Surface Chemistry, and Wettability

Abstract: Biomaterial surface characteristics are critical cues that regulate cell function. We produced a novel series of poly(l-lactic acid) (PLLA) and polystyrene demixed nanotopographic films to provide nonbiological cell-stimulating cues. The increase in PLLA weight fraction (phi) in blend solutions resulted in topography changes in spin-cast films from pit-dominant to island-dominant morphologies having nanoscale depth or height (3-29 nm). Lower molecular weight PLLA segregated to the top surface of demixed films,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 47 publications
3
106
0
4
Order By: Relevance
“…On a surface with grooves, osteoblastic cells expressed a higher RNA level of osteopontin and osteocalcin than on a flat surface [19]. Experiments using defined sizes of pits demonstrated that activity of alkaline phosphatase as a marker for osteogenic differentiation was more stimulated on 11 nm islands compared with 85 nm islands [20]. On the titanium nanotubes, tube diameters of 70 and 100 nm enhanced the expression of different osteogenic markers in mesenchymal stem cells compared with cells on a flat titanium surface [21].…”
Section: Cell Regulation By Physical Characteristics Of a Materials Tomentioning
confidence: 98%
“…On a surface with grooves, osteoblastic cells expressed a higher RNA level of osteopontin and osteocalcin than on a flat surface [19]. Experiments using defined sizes of pits demonstrated that activity of alkaline phosphatase as a marker for osteogenic differentiation was more stimulated on 11 nm islands compared with 85 nm islands [20]. On the titanium nanotubes, tube diameters of 70 and 100 nm enhanced the expression of different osteogenic markers in mesenchymal stem cells compared with cells on a flat titanium surface [21].…”
Section: Cell Regulation By Physical Characteristics Of a Materials Tomentioning
confidence: 98%
“…However, it was observed that contact angles decreased (water wettability increased) with either laser or mechanical treatment (presumably due to an increase in oxygen content on treated surfaces), indicating both topographic and surface-chemical modification. Lim et al [110,111] recently reported studies of hFOB adhesion and proliferation on polymer systems with varying surface texture, chemical composition, and wettability. As surfaces varied from smooth-to-textured with different topographic feature scale, hFOB adhesion was observed to exhibit statistically-significant differences in cell-substratum compatibility; although the full range in adhesion efficiency varied only about 20% among surfaces studied.…”
Section: Short-term Adhesion and Proliferation Of Hfob On Different Smentioning
confidence: 99%
“…For example, natural bone ECM (extracellular matrix) is a highly organized nano-composite consisting of, among other things, molecules of type-I collagen. Collagen type-I forms fibrils with an interfibrillar spacing of 68 nm and 35 nm depth [5] and a number of studies [6][7][8] have demonstrated that mimicking such roughness in vitro has beneficial effects on osteoblast proliferation. The role of the collagen fibrillar organization in controlling the arrangement of the actin cytoskeleton has sometimes been referred to as 'contact guidance' [9,10].…”
Section: Introductionmentioning
confidence: 99%